DESENVOLVIMENTO, CARACTERIZAÇÃO E AVALIAÇÃO BIOLÓGICA DE NANOPARTÍCULAS LIPÍDICAS CONTENDO CRISINA - Lima, Thiellen Wrobel Kultz de (2021)
Chrysin is a flavonoid widely found in bee plants and bee products such as honey and propolis. This natural product has been being studied by many researchers due to the broad spectrum of biological activities, such as anti-inflammatory, antioxidant, and antitumor activities, among others. Despite this broad spectrum of action, chrysin has low water solubility, low stability in biological fluids, and low cell adhesion, which can affect its absorption by the body. Nanotechnology is a tool that helps to reduce these effects, increasing solubility and stability characteristics of molecules, promoting enhancing delivery of the molecule to a specific site of action. Thus, this work aimed to develop a nanostructured system using a lipid matrix with methyl palmitate and ethyl palmitate for chrysin carrying through the high-shear homogenization technique. According to the development of factorial design, a formulation was optimized and characterized by evaluating the encapsulation efficiency, particle diameter, polydispersion index, zeta potential, and morphology by scanning electron microscopy technique. The optimized nanoparticle had a size of 332.8 nm, with a polydispersion index of 0.27 and an encapsulation efficiency of 99.28%. In the stability study, the system remained stable in suspension for only a month and a lyophilized system did not obtain proven stability. Toxicity tests against red blood cells and inhibition of the 2,2'-azinobis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS•+) radical were also evaluated. The results showed the effectiveness of the chrysin nanoparticle, with inhibition of approximately 72% to the hemolysis assay in 10 μg/mL. The nanoparticle was not toxic during the entire period of the study. The release assays in gastric (pH 1.2) and intestinal (pH 6.8) fluid and in phosphate buffer (pH 7.4) shows resulted in low percentages of release. It can be related to the metabolization of chrysin throughout the process. The pharmacokinetic assay demonstrated the efficiency of the chrysin encapsulation by the solid lipid nanoparticle formed, with improvement in the pharmacokinetic profile comparing to chrysin administered. Increasing the maximum concentration 141.56 ng/mL and 313.02 ng/mL for chrysin and chrysin nanoparticles, respectively. This work reveals the development and broad application potential of a chrysin-carrying lipid nanoparticle due to the innovation in using a lipid matrix composed of two distinct lipids and a prominent bioactive compound. The results obtained can be used as a basis for future research involving the association between methyl palmitate, ethyl palmitate, and chrysin.